Dengue em Minas Gerais: epidemiologia, análise de tendências e fatores associados ao óbito - Frederico Figueiredo Amancio (2014)
Introduction: The first reported case of dengue in the state of Minas Gerais occurred in 1987. In May 1996 the first cases were confirmed in the metropolitan region of the state. The disease spread fast resulting in the first major epidemic in 1998, with 147,418 reported cases. The metropolitan region of Belo Horizonte accounted for 87% of the reported cases. In 1999, the cases reduced greatly, but in the following year there was an increase, resulting in a greater occurrence of cases in 2002. The state had two major epidemics; 2010 and 2013, with approximately 250,000 and 500,000 reported cases. Despite the significant number of cases in the state, little is known of the epidemiology and disease trends. The objective of this study was to describe and analyze epidemiological trends in the state of Minas Gerais with emphasis on 2001-2010 period and assess potential factors associated with death by dengue. Methods: (i) ecological study of spatial analysis, time series, and case-series study conducted from data collected from Minas Gerais surveillance system, from 2001 to 2010, (ii) case study and (iii) case series of patients admitted to intensive care units. Secondary data source from the Information System for Notifiable Diseases (SINAN), Hospital Information System (SIH), and data from medical records were used. Results: Dengue, which is relatively recent in Minas Gerais, has resulted in three major epidemics (1998, 2010, 2013). From 2001 to 2010, 683,190 dengue cases were registered with 237 deaths. Dengue cases occur throughout the year with a tendency to increase in the months of November and December, with more notified cases in the months of March and April. The state presented an estimate of 3.79 (95% CI: 2.97; 4.71) deaths per 10,000 dengue cases reported. An increasing incidence occurred in all age groups, however the rate was greater in children under 15 years of age. While serotypes 1 and 2 predominated until 2002, from 2003-2008 there was a predominance of serotype 3. Young adults showed the highest occurrence during this period, however, patients 65 years or older had a higher risk of death. In 2011, serotype 4 was introduced for the first time in the state resulting in an outbreak in 2013. The first death due to dengue serotype 4 occurred in December 2012. The child was 11 years old with a history of autoimmune purpura. In 2013, the state reported its greatest epidemic, with significant DENV-4 contribution. The profile of deaths shows a high frequency of comorbidities and a higher risk of death in elderly groups ( 65 years old). From 2008 to 2013, 370 suspected cases of dengue in adults were admitted to the intensive care units. Mortality was 19.6% among the 97 laboratory confirmed cases included in this study. In-hospital mortality was significantly associated with Acute Physiology and Chronic Health Evaluation II and the Sequential Organ Failure Assessment score. Conclusion: The state has had annual increases in incidences of dengue cases. Although there has been a rise in the proportion of children affected with dengue under 15, the elderly still pose the highest risk of death.